New Chaos-Based Lossless Image Compression and Selective Encryption Using Alpha Rooting - Rajamandrapu Srinivas, M. Venkateswarlu (International Journal of Advanced Science and Technology, 2020)
Secure image-encryption techniques are developed by an efficient and new method in this proposed paper. The combination of encryption and compression techniques is introduced in a new algorithm. In this algorithm, the decomposition of image and decorrelation of its pixels in to approximation and detailed component are done by using wavelet transform.  A chaos-based algorithm of encryption is used to encrypt the approximation component (the more important component). This algorithm produces a good diffusion and confusion properties of cipher for test image. The Wavelet transform is used to compress the detail components (the remaining components). High level of security is provided by this proposed algorithm. A complete specification for the new algorithm is provided. The validity of proposed system is demonstrated by using several test images. For real-time image encryption and transmission, the proposed algorithm of several experiments on image crypto systems results an approach of efficient and secure Systems. Keywords: Chaos-based image encryption, alpha rooting algorithm, wavelet transform, chaotic maps.